Law Between Utopia and Reality - Trajković, Marko; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
Abstract: The tension in which our idea of law finds itself occurs between “is” and “ought,” that is, between our reality and social and personal utopia, or between desire and reality. This simultaneously provokes a struggle for better law. However, in that struggle for better law it may happen that utopian aspirations themselves give rise to dogmas about which no further debate is possible. In a certain way, it then seems that we once again have some command resembling the command of a sovereign that is not open to discussion. It may then appear that the only thing left to us is to look to the heavens. Perhaps the answer lies in the possibility of a reasoned critique of what is given to us, even when it is a norm of an imperative character. In these constant attempts to move between the command of the sovereign as a source of law and the sources of law that stand in the realm of values, we continually find ourselves in a state of tension between “is” and “ought,” and this tension will neither diminish nor cease to exist. Such a gap, expressed in desire and possibilities, has brought about a spirit of social insecurity from which an unfounded faith in legal positivism was later born. These cyclical circles arising between “is” and “ought” have never diminished, and even less disappeared, especially not in the field of criminal law.